Analysis of Physics Science Literacy in the Duanu Tribe's Shellfishing Tradition of Junior High School Students - adzkia, vira; Zulirfan, Z.; Sahal, Muhammad (Journal of Indonesian Science Teachers, 2025)
Shellfish (Menongkah Kerang) scientific literacy is the ability to understand physics concepts and processes integrated with local culture and wisdom in Tanah Merah, Riau. Menongkah kerang activities are one of the cultures that have existed for generations in Tanah Merah, Riau and it has been identified that menongkah kerang activities have scientific potential that can be explained scientifically. This research aims to identify the level of physics literacy of the menongkah kerang tradition of students at SMP Negeri 1 Tanah Merah, SMP Negeri 3 Tanah Merah and MTS YPI Kuala Enok. The type of research used is survey research with a quantitative descriptive approach. The sample in the study was 158 students consisting of 76 male students and 82 female students. The instrument in this research was a physics science literacy test on menongkah kerang which consisted of 20 multiple-choice questions with a KR-20 reliability coefficient of 0.74. Descriptive analysis techniques were used to determine the level of physics science literacy in the shellfishmenongkah kerang competition sub-context. The results of descriptive and inferential analysis show that the level of physics science literacy of Menongkah Kerang students has an average total score of 52.27. Based on gender, it was identified that male students have better physics science literacy skills than female students. There are differences in scores based on gender, there are significant differences. In general, it is concluded that the level of physics science literacy of Junior High School students in Tanah Merah District in the menongkah kerang activity is still in the low category and gender affects the level of students' science literacy.